1991
DOI: 10.1111/j.1432-1033.1991.tb16395.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the orientations of tryptophan analogues bound to the trp repressor and the relationship to activation

Abstract: The antirepressor indole 3-propanoate has been shown by X-ray crystallography to bind in a different We have used visible absorption and 'H-NMR spectroscopy to characterise the nature of several ligandrepressor complexes and DNA-binding assays to assess the relative operator binding affinities. 5-Fluorotryptophan binds with similar affinity and in the same orientation as L-tryptophan, and is an equally effective corepressor. In contrast, the tight-binding antirepressor indole 3-acrylate binds in the same orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…The ability to protect the operator in vitro and repress trpBA expression in vivo is a function of the affinity of TrpR for the various corepressors and/or the affinity of the TrpR/corepressor complex for the operator DNA sequence. In E. coli , it has been shown that 5‐fluorotryptophan binds with similar affinity and in the same orientation as l ‐tryptophan, and is an equally effective corepressor (Borden et al ., 1991). In addition, different tryptophan analogues have varying affinities for purified TrpR and the subsequent analogue–TrpR complexes show differential binding affinities for the E. coli operator sequence (Marmorstein and Sigler, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to protect the operator in vitro and repress trpBA expression in vivo is a function of the affinity of TrpR for the various corepressors and/or the affinity of the TrpR/corepressor complex for the operator DNA sequence. In E. coli , it has been shown that 5‐fluorotryptophan binds with similar affinity and in the same orientation as l ‐tryptophan, and is an equally effective corepressor (Borden et al ., 1991). In addition, different tryptophan analogues have varying affinities for purified TrpR and the subsequent analogue–TrpR complexes show differential binding affinities for the E. coli operator sequence (Marmorstein and Sigler, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Some tryptophan analogues bind more tightly to the aporepressor than does tryptophan, induce the conformational change, and yet these form protein-ligand complexes or pseudorepressors that cannot bind to DNA (Marmorstein et al, 1987;Marmorstein & Sigler, 1989). For example, the tryptophan analogue, indole-3-propionate (IPA), lacks the positively charged amino group found on tryptophan and binds to the protein using a different binding mode than tryptophan Borden et al, 1991). Lawson and co-workers proposed that the IPA binding mode would interfere with pseudorepressor-DNA binding due to steric and electrostatic clashes between the IPA carboxylate and a DNA backbone phosphate.…”
mentioning
confidence: 99%
“…We have previously reported that the mobility of the 1 : 1 trp holorepressor: trpO complex is not dependent on the nature of the corepressor (Borden 1991). However, the different apparent sizes of the various complexes that are formed are dependent on the nature of the DNA target, particularly the 1 : 1 complexes or the holorepressor with trpO and aroH.…”
Section: Discussionmentioning
confidence: 99%
“…Trp aporepressor was purified from an overproducing mutant as previously described (Joachimiak et al 1983, Borden et al 1991. The protein was > 95% pure judging from SDS electrophoresis.…”
Section: Methodsmentioning
confidence: 99%